Primary melanoma of the uterine cervix figo stage III B - Teixeira, Júlio César; Salina, José Roberto; Teixeira, Luiz Carlos; Andrade, Liliana Aparecida Lucci De Angelo (São Paulo Medical Journal, 1998)
The primary malignant melanoma of the uterine cervix is rare, usually diagnosed at an advanced stage and with poor prognosis. The diagnosis is made through histological evaluation and confirmed by special staining procedures. Radical surgery has been used and advocated. However in its advanced stages chemotherapy, immunotherapy or radiotherapy can be employed. A case of a patient with malignant melanoma of the uterine cervix, Stage IIIb, is presented in addition to a clinical and pathological discussion.